Targeted imaging of pulmonary fibrosis by a cyclic peptide LyP-1 - Jing Li; Rui Shu; Tian Peng; Zifeng Yang; Mingzi Yang; Fengjiao Hu; Zhangqian Tao; Ying Hong; Zhiwei Cai; Jing Jia; Lu Wan; Song Tian; et al. (Scientific Reports)
Abstract Pulmonary fibrosis (PF) is an interstitial chronic lung disease characterized by interstitial inflammation and extracellular matrix deposition, resulting in progressive lung dysfunction and ultimate respiratory failure. However, lacking of precise and noninvasive tracers for fibrotic lesions limits timely diagnosis and treatment. Here, we identified LyP-1, a cyclic peptide, as a specific and sensitive tracer for PF detection using PET/CT imaging. FITC-LyP-1 selectively recognized fibrotic regions in bleomycin-induced PF mice, indicating its targeting capability. The colocalization of FITC-LyP-1 with extracellular collagen I within the fibrotic lesions validated its specificity, and further analysis revealed several potential target molecules. In the in vivo application studies, radiolabeled [68Ga]Ga-LyP-1 showed significantly increased lung uptake in PF mice, specifically enriching fibrotic regions on PET/CT imaging. Notably, compared to CT imaging that showed increased mean lung density throughout the phases after bleomycin-administration, lung uptake of [68Ga]Ga-LyP-1 was only increased in the later phase, indicating that LyP-1 recognizes the fibrous changes rather than the inflammatory cells in vivo. These results suggest that the new radiotracer [68Ga]Ga-LyP-1 specifically detects the extracellular matrix in fibrotic lungs. LyP-1 shows promise as a noninvasive tracer for assessing human pulmonary fibrosis, offering potential for improved diagnostic accuracy and timely intervention.